2019
DOI: 10.1051/matecconf/201930015005
|View full text |Cite
|
Sign up to set email alerts
|

Including the normal to shear stresses ratio in fatigue life estimation for cyclic loadings

Abstract: The paper presents the estimation of the fatigue life under multiaxial cyclic loading of two construction materials. The main aim of this paper is to present a new method which allows evaluation of fatigue life during the design and construction phase of machine elements. In paper three well known multiaxial fatigue criteria based on the critical plane approach verified. This paper contains a proposition to define a new way of determining an orientation angle of the critical plane. The comparison between exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…As mentioned earlier, the full fatigue characteristics according to Equations ( 5) and (9) will not be used in this work because the aluminum alloys analyzed behave like practically elastic bodies in a wide range. Previous [45,46] analyses for these materials show that even at maximum loads in the analyzed tests the assumption of an elastic-plastic body significantly hinders the modelling of fatigue strength and the decrease in stress amplitude is only 2 MPa, which corresponds to very slight plastic strain and, consequently, a minimal increase in total strain. Therefore, simplified formulas analogous to Basquin's model were used for normal strain for oscillatory pendulum bending:…”
Section: Discussion Of Comparison Of Strain Fatigue Characteristicsmentioning
confidence: 91%
See 1 more Smart Citation
“…As mentioned earlier, the full fatigue characteristics according to Equations ( 5) and (9) will not be used in this work because the aluminum alloys analyzed behave like practically elastic bodies in a wide range. Previous [45,46] analyses for these materials show that even at maximum loads in the analyzed tests the assumption of an elastic-plastic body significantly hinders the modelling of fatigue strength and the decrease in stress amplitude is only 2 MPa, which corresponds to very slight plastic strain and, consequently, a minimal increase in total strain. Therefore, simplified formulas analogous to Basquin's model were used for normal strain for oscillatory pendulum bending:…”
Section: Discussion Of Comparison Of Strain Fatigue Characteristicsmentioning
confidence: 91%
“…This could be done this way because although these characteristics are not parallel, they do not differ significantly from this parallelism (0.118/1.208 and 0.213/0.188 for 2017A and 6082, respectively). The oscillatory bending characteristics and bilateral torsion are almost parallel, which is very important [46], but the individual calculations in the last two columns of the table mentioned above were made for fatigue strength from about the middle part of the determined characteristics, that is, for 105 cycles. Earlier analyses [47] showed that the ratio τ f /σ f theoretically fits in the range of…”
Section: Discussion Of Comparison Of Strain Fatigue Characteristicsmentioning
confidence: 99%